Estrutura do conteúdo dos exercícios de competição das ginastas portuguesas de elite e ginastas finalistas das Taças do Mundo - Batista, A.; Garganta, R.; Avila-Carvalho, L (Portuguese Journal of Sport Sciences, 2018)
The aim of this study was to compare the content structure of competitive routines of finalists` gymnasts of the World Cups of Lisbon (2013 and 2014) and Portuguese gymnasts present in competition. The sample consisted of 21 finalists` gymnasts and eight Portuguese gymnasts. The content of 96 individual competitive routines was analyzed according to the Code of Points (2013-2016). The results showed that the finalists and Portuguese gymnasts presented similar number and value of the body difficulties of jumps and balances, as well as a smilar number of body difficulties of rotations. However, the finalists` gymnasts presented a higher number and value of body difficulties, total value of rotation difficulties; number of turns (rotational degrees) in rotation elements, number of difficulties in series, multiple and mixed. The groups revealed a similar number of dance steps and dynamic rotation elements, however, the finalists` gymnasts presented a higher number of number of elements of the fundamental apparatus technical groups during the dance steps, as well as higher number of body rotations, total number of additional criteria and number of rotation criteria in the dynamic rotation elements. Furthermore, the Portuguese gymnasts presented a higher number of masteries elements in comparison to finalists` gymnasts.